A Study on Image Quality Improvement for 3D Pagoda Restoration - Lee, Byong-Kwon (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The SRGAN algorithm based on the Generative Adversarial Networks (GANS) algorithm is used for image generation, image restoration, and resolution improvement. In this study, we proposed a method to improve the quality of pagoda images to create a 3D model by combining several 2D pagoda images. In the study, the SRGAN artificial intelligence algorithm was used to minimize the noise generated when converting low-quality images into 3D models. Low resolution, high resolution and super resolution results were obtained with the SRGAN algorithm by selecting the low quality of the Pagoda image dataset. In addition, the degree of resolution improvement was confirmed by collecting quantified R, G, and B information through histogram analysis. The research results will be used as a dataset for converting 2D images into 3D models.